2010
DOI: 10.1002/14651858.cd006827.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Incision and drainage of perianal abscess with or without treatment of anal fistula

Abstract: The published evidence shows fistula surgery with abscess drainage significantly reduces recurrence or persistence of abscess/fistula, or the need for repeat surgery. There was no statistically significant evidence of incontinence following fistula surgery with abscess drainage. This intervention may be recommended in carefully selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 13 publications
0
43
1
Order By: Relevance
“…Quah et al (6) performed a meta-analysis including 405 patients from five clinical studies, which could not demonstrate the superiority of fistula surgery without sphincter salvage over incision and drainage, and stated that randomized studies were required. However, a series published in 2010 including 479 patients showed that fistula surgery applied simultaneously with abscess drainage reduced the recurrence rate (5). Also, in our study, 10 patients identified to have fistula during drainage received simultaneous fistulotomy and no recurrences could be identified in their one-year follow-up.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Quah et al (6) performed a meta-analysis including 405 patients from five clinical studies, which could not demonstrate the superiority of fistula surgery without sphincter salvage over incision and drainage, and stated that randomized studies were required. However, a series published in 2010 including 479 patients showed that fistula surgery applied simultaneously with abscess drainage reduced the recurrence rate (5). Also, in our study, 10 patients identified to have fistula during drainage received simultaneous fistulotomy and no recurrences could be identified in their one-year follow-up.…”
Section: Discussionmentioning
confidence: 43%
“…The reason for this could be that the patients, who had the above-mentioned characteristics that would cause anorectal abscess development, were not included in the study, the number of patients was limited and the patients who developed recurrence preferred specialized centers. In a current meta-analysis, it was reported that the shortest follow-up period was 12 months and the longest follow-up period was 42.5 months for the included studies (5). The median follow-up period in our study was identified to be 9 months; the recurrence rate might have been found to be low on account of this short followup period.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…25 In spite of evidence suggesting that treating an associated fistula in the acute setting reduces subsequent recurrence, 26 there is insufficient consensus to support surgeons undertaking immediate fistula treatment at incision and drainage of perianal abscesses, particularly if they are less experienced.…”
Section: Incision and Drainagementioning
confidence: 99%
“…There has been much controversy whether all abscesses should be treated like fistula to lower recurrence rate. In a Cochrane database published in 2010 [3], six trials were identified, involving 479 subjects, comparing incision and drainage of perianal abscess alone versus incision and drainage with fistula treatment. The authors concluded that fistula surgery with abscess drainage significantly reduces recurrence or persistence of abscess/fistula, or the need for repeat surgery.…”
Section: Fistulas With Multiple Openings Are Tuberculus In Originmentioning
confidence: 99%